1967
DOI: 10.1021/ie50689a007
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Sensitivity in Fitting Nonlinear Kinetic Models

Abstract: The practical considerations important for the estimation of parameters in the nonlinear hyperbolic classes of kinetics are presented. The sums of squares surfaces of several example cases are examined to disclose the characteristics of these surfaces important in nonlinear parameter estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1968
1968
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…(2) gives the traditional kinetic model. Studies of changes in the form of parameters to the Arrhenius equation can be found in Mezak and Kittrell [15]. Draper and Smith [16] analyzed aspects of reparameterization and also made reference to an equation of this type.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) gives the traditional kinetic model. Studies of changes in the form of parameters to the Arrhenius equation can be found in Mezak and Kittrell [15]. Draper and Smith [16] analyzed aspects of reparameterization and also made reference to an equation of this type.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Draper and Smith [16] analyzed aspects of reparameterization and also made reference to an equation of this type. The reparameterization performed in this work [15] was based on the following transformations of Eq. (3)…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…3͒, it is informative to know the level of confidence of the estimates. A confidence region of the estimates, 26,29 in which the true parameter values are expected to reside, can be shown as a contour of the value ͑S͑k͒͒ given in Eq. 4.…”
Section: Numerical Detailsmentioning
confidence: 99%
“…Dieses Kriterium wurde in analoger Weise auch von HanEil, Mitschka und Beranek [27], von H a j e k , D u c h e t und K o c h l o e f l [42] und von Mezaki und Kittrell [29] benutzt. Es mussen alle Modelle als gultig betrachtet werden, deren Fehlerquadratsumme kleiner Qkril ist.…”
Section: Mathematische Behandlung Der Datenunclassified